A mixture of routinely encountered xenobiotics induces both redox adaptations and perturbations in blood and tissues of rats after a long-term low-dose exposure regimen: The time and dose issue. (15th December 2019) - Fountoucidou, Polyxeni; Veskoukis, Aristidis S.; Kerasioti, Efthalia; Docea, Anca Oana; Taitzoglou, Ioannis A.; Liesivuori, Jyrki; Tsatsakis, Aristidis; Kouretas, Demetrios
Graphical abstract: Highlights: The effects of long-term low-dose exposure to a chemical mixture on redox biomarkers in rats were evaluated. The mixture induces physiological redox adaptations in all three doses (below NOAEL) in blood after 12 months of exposure. The dose of the mixture at 0.05 × NOAEL causes remarkable redox perturbations in blood and tissues after 18 months of exposure. This study points out the effects of low-dose long-term combined stimuli in redox status. Abstract: Exposure of humans to xenobiotic mixtures is a continuous state during their everyday routine. However, the majority of toxicological studies assess the in vivo effects of individual substances rather than mixtures. Therefore, our main objective was to evaluate the impact of the 12- and 18-month exposure of rats to a mixture containing 13 pesticides, food, and life-style additives in three dosage levels (i.e. 0.0025 × NOAEL, 0.01 × NOAEL, and 0.05 × NOAEL), on redox biomarkers in blood and tissues. Our results indicate that the exposure to the mixture induces physiological adaptations by enhancing the blood antioxidant mechanism (i.e., increased glutathione, catalase and total antioxidant capacity and decreased protein carbonyls and TBARS) at 12 months of exposure. On the contrary, exposure to the 0.05 × NOAEL dose for 18 months induces significant perturbations in blood and tissue redox profile (i.e., increased carbonyls and TBARS). This study simulates a scenario of real-life risk exposure to mixtures of xenobiotics through a long-term low-dose administration regimen in rats. The results obtained could support, at least in part, the necessity of introducing testing of combined stimuli at reference doses and long term for the evaluation of the risk from exposure to chemicals.